Genome-wide identification and expression analysis of the mating-responsive genes in the male accessory glands of Spodoptera litura (Lepidoptera: Noctuidae) - R. Mamtha; Tannavi Kiran; Vivek Chandramohan; B. S. Gowrishankar; D. Manjulakumari (Journal of Genetic Engineering and Biotechnology, 2023)
Abstract Background Mating elicits significant changes in gene expression and leads to subsequent physiological and behavioural modifications in insects. The reproductive success of both sexes is contributed immensely by the male accessory gland (MAG) proteins that are transferred along with sperms to the female reproductive tract during mating where they facilitate several processes that modify the post-mating behaviour. The mating-responsive genes in the MAGs have been identified and reported in many insects but have not been well-characterized in the important agricultural pest Spodoptera litura. Here, we present RNA sequencing analysis to identify mating-responsive genes from the accessory glands of virgin males and males interrupted during mating. Results Overall, 91,744 unigenes were generated after clustering the assembled transcript sequences of both samples, while the total number of transcripts annotated was 48,708 based on sequence homology against the non-redundant (NR) database. Comparative transcriptomics analysis revealed 16,969 genes that were differentially expressed between the two groups, including 9814 up-regulated and 7155 down-regulated genes. Among the top 80 genes that were selected for heat map analysis, several prominent genes including odorant binding protein, cytochrome P450, heat shock proteins, juvenile hormone binding protein, carboxypeptidases and serine protease were differentially expressed. Conclusions The identified genes are known or predicted to promote several processes that modify the female post-mating behaviour. Future studies with the individual MAG protein or in combination will be required to recognize the precise mechanisms by which these proteins alter female physiology and reproductive behaviour. Thus, our study provides essential data to address fundamental questions about reproduction within and among insects and also paves way for further exploration of the functions of these proteins in female insects.